(untitled) - Swift, Donald R. (Oxford, 1993)
A practical introduction to aquaculture for those who are new to fish farming or have become involved in farming a different species. The first part covers the basic biology of those fish and shellfish which are commonly farmed, their frowth, nutrition and reproduction, and also outlines the various methods of farming. The second part deals specifically in more detail with the farming of salmonids, catfish, tilapia, carp, milkfish, mullet, turbot, marine prawns, freshwater prawns, oysters, mussels, eels and scallops.
Keywords: Aquaculture